2022
DOI: 10.3390/min13010040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Shape on Parameter Calibration for a Discrete Element Model for Mining Applications

Abstract: The discrete element method (DEM) has been widely employed to model processes in different industries, such as mining, agriculture, pharmaceuticals, and food. One of the main lines of research, and in which different authors propose several approaches, is the calibration of parameters. Bulk calibration (BCA) is a common approach used that does not necessarily represent the individual behavior of each particle. On the other hand, direct measurement (DMA) is another approach employed in some cases. This work pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the specimen preparation phase, the dimensions of the box were defined, and spheres were randomly distributed inside the box using The mechanical behavior of granular materials is significantly influenced by the shape of their particles. However, using non-spherical particles in simulations can be computationally intensive and require significant storage capacity [36,37]. Nevertheless, recent research has demonstrated that using sphere particles with appropriate rolling friction can lead to similar effects as non-spherical particles while reducing both storage requirements and computational time [21,37,38].…”
Section: Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…In the specimen preparation phase, the dimensions of the box were defined, and spheres were randomly distributed inside the box using The mechanical behavior of granular materials is significantly influenced by the shape of their particles. However, using non-spherical particles in simulations can be computationally intensive and require significant storage capacity [36,37]. Nevertheless, recent research has demonstrated that using sphere particles with appropriate rolling friction can lead to similar effects as non-spherical particles while reducing both storage requirements and computational time [21,37,38].…”
Section: Model Setupmentioning
confidence: 99%
“…Several researchers have conducted calibration chamber and centrifuge tests on carbonate sands to better understand what happens when a pile is driven into weak sands [ 5 , 6 , 7 , 8 ]. This phenomenon has also attracted many researchers to conduct laboratory tests to study the influence of particle breakage on the critical state behaviors, shear stress ratios and dilatancy of granular soils [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] as well as numerical modeling [ 14 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation